2010
DOI: 10.1111/j.1744-7909.2010.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically Distinct Cellulose Synthase Genes Support Secondary Wall Thickening in Arabidopsis Shoot Trichomes and Cotton Fiber

Abstract: Through exploring potential analogies between cotton seed trichomes (or cotton fiber) and arabidopsis shoot trichomes we discovered that CesAs from either the primary or secondary wall phylogenetic clades can support secondary wall thickening. CesA genes that typically support primary wall synthesis, AtCesA1,2,3,5, and 6, underpin expansion and secondary wall thickening of arabidopsis shoot trichomes. In contrast, apparent orthologs of CesA genes that support secondary wall synthesis in arabidopsis xylem, AtCe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 50 publications
5
78
0
Order By: Relevance
“…There are even examples of convergent evolution of secondary cell walls within the angiosperm lineage. Cotton (Gossypium hirsutum) fiber secondary cell walls are synthesized by the same CESAs that are responsible for secondary cell wall deposition in tracheary elements and fibers , whereas the secondary cell walls of epidermal trichomes are synthesized by the primary CESAs (Betancur et al, 2010). These observations are consistent with independent evolutionary origins for secondary cell walls in different land plant lineages and different cell types within angiosperm lineages.…”
Section: Mosses and Vascular Plants Have Acquired Similar Secondary Csupporting
confidence: 77%
“…There are even examples of convergent evolution of secondary cell walls within the angiosperm lineage. Cotton (Gossypium hirsutum) fiber secondary cell walls are synthesized by the same CESAs that are responsible for secondary cell wall deposition in tracheary elements and fibers , whereas the secondary cell walls of epidermal trichomes are synthesized by the primary CESAs (Betancur et al, 2010). These observations are consistent with independent evolutionary origins for secondary cell walls in different land plant lineages and different cell types within angiosperm lineages.…”
Section: Mosses and Vascular Plants Have Acquired Similar Secondary Csupporting
confidence: 77%
“…Our previous studies also showed that trichomes and pellucid dots were expressed well on plants that grew with low amounts of soil water (Yamawo, Hada & Suzuki 2012) and low nutrient conditions (Yamawo Bryant et al 1987). Trichomes fundamentally consist of cellulose (Betancur et al 2010). Pellucid dots typically contain toxic metabolic substances or essential oils (Wittstock & Gershenzon 2002;Schilmiller, Last & Pichersky 2008;Sirikantaramas, Yamazaki & Saito 2008).…”
Section: Discussionmentioning
confidence: 91%
“…It has a composition similar to the primary wall, although the cellulose content is slightly higher and the cellulose microfibrils are oriented in a cross-hatched, shallow helix along the longitudinal cell axis (Meinert and Delmer 1977;Wakelyn and French 2007). The genetic program supporting secondary wall cellulose synthesis is similar to the one used in sclerenchyma cells of the plant body (Betancur et al 2010), although cotton fiber secondary walls lack lignin and extensive matrix components. Toward the end of cotton fiber development, there is an ill-defined 'maturation' phase before the boll opens to allow final drying of the fiber in air (Haigler et al 2012).…”
Section: Introductionmentioning
confidence: 98%